Educational Activity and Life Satisfaction of People in Senior Age - Bursová, Janka; Cherchowska, Justyna; Budayová, Zuzana; Maturkanič, Patrik (Journal of Education Culture and Society, 2024)
Aim. The main objective of the authors of the contribution is to submit the description of the subjective satisfaction of seniors with their lives in connection with education at the third age universities. The authors identify areas of motivation for education, barriers that may occur in this education. They also point out the knowledge and experience that seniors gain in education at the Senior universities.Methods. The analysis of the cited research results indicates subjective feelings and opinions about the satisfaction of seniors with their life and educational activities, the participation of seniors in activities offered by the Senior University (SU).Results. In the article, the authors present the results of a research project aimed at investigating the subjective life satisfaction of senior university students in the context of their education at the university, they point to the life satisfaction of seniors through quantitative research.Conclusion. Participation in the different types of activities offered by the Senior University is determined by socio-demographic factors such as the length of time seniors attend third-age universities (the Senior University), the length of time they attend classes, education level, age and other factors. Also interesting are the motives of seniors to use the offers of those universities, which are related to the desire to spend time in an interesting way, opportunities to acquire new knowledge and skills, opportunities to establish new friendships and opportunities to get involved in life.